Ability to alter song in two grassland songbirds exposed to simulated anthropogenic noise is not related to pre-existing variability. Issue 2 (3rd April 2018) - Curry, Claire M.; Antze, Bridget; Warrington, Miyako H.; Des Brisay, Paulson; Rosa, Patricia; Koper, Nicola
Abstract: Organisms encounter noise naturally in the environment. However, increasing prevalence of human-caused noise seems to be resulting in behavioural changes in many animals that can affect survival and reproduction. Not all species react the same way to noise; some adjust their vocal signals while others do not. We hypothesized that species with more variability in their vocal signals would be better able to adjust their signals to be audible over anthropogenic noise. We tested this within a large-scale manipulative experiment by recording songs of two grassland songbirds, Baird's sparrow ( Ammodramus bairdii ) and Savannah sparrow ( Passerculus sandwichensis ), both of which are found in areas increasingly affected by energy extraction noise. We compared these species because Savannah sparrows have more variability in their songs geographically and temporally compared to Baird's sparrows. We recorded both species' songs before, during and after high-fidelity playbacks of oil well drilling noise. Surprisingly, both species changed parts of their songs in the presence of noise (Baird's sparrow usually decreasing frequency and Savannah sparrow increasing frequency) and these changes were not related to seasonal, song, or syllable variability. We suggest instead that acoustically heterogeneous environments may favour the evolution of species that are capable of adjusting their songs in response to variable ambient noise.